Young people at the margins in Pretoria Central: Are the faith-based organisations making a difference? - Swart, Ignatius (HTS teologiese studies, 2019)
The authors’ recent case study work in Pretoria Central as part of the international research project ‘Youth at the margins’ (YOMA) constitutes the focus of this article. From this vantage point, the authors offer a presentation of their research findings in order to ultimately answer the question ‘to what extent the faith-based organisations (FBOs) are making a difference in the lives of young people at the margins in this particular case study locality (Pretoria Central)’. The article begins by contextualising the lives of young people in Pretoria Central against the backdrop of far-reaching socio-economic, demographic and religious change in the area since the end of the apartheid era. After explaining the case study methodology and offering a brief profile of the research participants, the discussion then proceeds with a more detailed discussion of distinctive aspects of the case study findings. In the conclusion, the authors argue that the answer to the article’s guiding question seems to be a negative one when the reality of young people’s seemingly permanent structural exclusion is considered. At the same time, this verdict does not withhold them to also conclude with appreciative remarks about the role that churches and FBOs of the non-governmental organisation (NGO) type are playing with respect to marginalised young people in Pretoria Central.